3D Printing of Polymeric Bioresorbable Stents: A Strategy to Improve Both Cellular Compatibility and Mechanical Properties - Sousa, Ana M. (2022)
One of the leading causes of death is cardiovascular disease, and the most common cardiovascular disease is coronary artery disease. Percutaneous coronary intervention and vascular stents have emerged as a solution to treat coronary artery disease. Nowadays, several types of vascular stents share the same purpose: to reduce the percentage of restenosis, thrombosis, and neointimal hyperplasia and supply mechanical support to the blood vessels. Despite the numerous efforts to create an ideal stent, there is no coronary stent that simultaneously presents the appropriate cellular compatibility and mechanical properties to avoid stent collapse and failure. One of the emerging approaches to solve these problems is improving the mechanical performance of polymeric bioresorbable stents produced through additive manufacturing. Although there have been numerous studies in this field, normalized control parameters for 3D-printed polymeric vascular stents fabrication are absent. The present paper aims to present an overview of the current types of stents and the main polymeric materials used to fabricate the bioresorbable vascular stents. Furthermore, a detailed description of the printing parameters' influence on the mechanical performance and degradation profile of polymeric bioresorbable stents is presented.